1952
DOI: 10.1103/physrev.88.92
|View full text |Cite
|
Sign up to set email alerts
|

Electronic States in Crystals under Large Over-All Perturbations

Abstract: points the spike rarely settles, but oscillates about the surface with great rapidity. With steel points, on the other hand, the discharge frequently anchors itself to one spot, and there remains quite steady, only moving about when the field is increased almost to Qashover. It is not unusual for the stem to take up a position off, and inclined to, the axis of symmetry. When the point is subsequently examined under the microscope it is usually found that the spot favored by the root of the discharge, coincides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1956
1956
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…dq 2π e −iτ sin(q−ϕ)+iqn = e iϕn J n (τ ). (19) with ϕ = arctan(t/λ). Thus, up to phase factors the quantities F n are Bessel functions with argument τ , a fact which was not realized in [13].…”
Section: Chainmentioning
confidence: 99%
“…dq 2π e −iτ sin(q−ϕ)+iqn = e iϕn J n (τ ). (19) with ϕ = arctan(t/λ). Thus, up to phase factors the quantities F n are Bessel functions with argument τ , a fact which was not realized in [13].…”
Section: Chainmentioning
confidence: 99%
“…Zak (1968) has further stated that even in the most favourable case for the existence of a ladder, a one-band linear tight-binding chain, none could result. Other workers, such as Feuer (1952) and Hacker and Obermair (1970), have examined the infinite linear chain and find ladder-like behaviour, and Shockley (1972) suggested that, under certain conditions, this may be true even for finite crystals.…”
Section: H ( R ) $ ( V + Nu) = ( E + Nef U ) $ ( V + Na)mentioning
confidence: 99%
“…have been discussed for an infinite chain by Feuer (1952) and Hacker and Obermair (1970). In this case.…”
Section: Numerical Solution Of Eigenvalue Problemmentioning
confidence: 99%
“…The electronic stationary states in a periodic potential with period d in the presence of an external dc electric field E dc are localized in a one-band approximation and have energies E n ϭE 0 ϩenE dc d, where n is an integer. 25 These equally spaced states form the so-called Wannier Stark ladder ͑WSL͒ in the BSSL; they were first evidenced experimentally by Mendez et al, 26 and have been theoretically treated with the inclusion of excitonic effects by a number of authors. [27][28][29][30] Shortly after the experimental observation of the WSL states, the dynamical behavior of excitons in BSSL's were investigated both theoretically 31 and experimentally.…”
Section: Introductionmentioning
confidence: 99%